O INSTITUTO HISTÓRICO E GEOGRÁFICO DE PALMEIRA E A COLÔNIA CECÍLIA – 1955-2014 - NASCIMENTO, JOSIMAR DE JESUS VITOR DO (2021)
This work aims to analyze the role of the Historical and Geographical Institute of Palmeira, as well as the historiographic production of some of its members on the anarchist experience called Colônia Cecília, which took place in the municipality of Palmeira, in the late nineteenth century. Over the years, Colônia Cecília has become the object of numerous written and audiovisual productions, but it has also been discussed by writers who are members of the IHGP. Founded on February 13, 1955, the Historical and Geographical Institute of Palmeira was created under the stimulus of the Historical Institute of Paranaguá/PR. Private institution, with a statutory mission, the study of historical and geographical aspects, the study of cultural and linguistic aspects, the cult of local and regional traditions, in addition to proposing to receive, organize and preserve historical objects through its collection and extol personalities and facts of local history.